Summary of Operational Rations - Mason, Vera C; Meyer, Alice I; Klicka, Mary V (1982)
This study was conducted to provide baseline data (acceptance, nutrition, stability, utility, weight and cube data, heating and water requirements) on past and existing military operational rations/foods to assist in systems analyses for development of new ration concepts to meet future Marine Corps requirements. Operational rations include: general operation rations, special operational subsistence, survival subsistence and ration supplements. Information provided for each ration includes components, requirements for preparation, shelf life, weight and cube information, as well as advantages and disadvantages.